The Effectiveness Of Applying Inductive Approach In Teaching Grammar For Senior High School Students In North Aceh - Rasyimah, Rasyimah (PASAI, 2014)
This research was aimed to find out how applying inductive approach in teaching grammar makes the language learning more effective for senior high school students, particularly in North Aceh. The inductive approach represented a more modern style of teaching where the new grammatical structures or rules are presented to the students in real language context. The students learned the use of the structure through practice of the language in context, and later realize the rules from the practical examples. From the research conducted in one particular high school in North Aceh district, there were significant differences between the students who were taught with inductive approach as an approach in teaching grammar. So, it was summarized that the students who were taught with inductive approach gave better results than the students who werenât.